Pengaruh spesialisasi auditor, maturitas utang, konservatisme Akuntansi, dan kualitas laporan keuangan terhadap efisiensi investasi - Maulina Devi, Agitha Rizky; Praptapa, Agung; Farida, Yusriyati Nur (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to determine the effect of auditor specialization variables, debt maturity, accounting conservatism, and the quality of financial reports on investment efficiency practices in property and real estate sector companies. The investment efficiency measurement model is measured by growth opportunity measurements. This type of research is quantitative, using secondary data in the form of annual reports from property and real estate companies listed on the Indonesia Stock Exchange. The results of this study indicate that the variables of auditor specialization and accounting conservatism have a positive and significant effect on investment efficiency, while the financial report quality variable has a positive but insignificant effect on investment efficiency. In addition, the debt maturity variable has a negative and insignificant effect on investment efficiency for property and real estate companies listed on the Indonesia Stock Exchange.